Budget based bonus, budget emphasis, budget gaming, and the impact on budget value - Rhaisya Setiawati Rachmat; SeTin SeTin (Jurnal Keuangan dan Perbankan, 2020)
The issue of budget value has received attention and criticism from many researchers, especially that the budget value is not aligned with the sacrifices made in the budgeting process. The purpose of the study is to examine the effect of budget-based bonus and budget emphasis towards budget gaming and its implications on budget value. A questionnaire survey was used for data collection and was collected by personal and online (via email/link) to managers who have joined the Indonesian Management Association. Non-probability sampling method was used for the sample selection. A total of 286 data were collected and could be analyzed. Data were analyzed using Partial Least Square. The results show that budget emphasis affects budget gaming and also affects budget value. But budget-based bonus has no effect neither towards gaming budget nor budget value. This research enriches the budgeting literature especially for the context in Indonesia and enriches the findings of budget practices in the world. The results contribute to practitioners in making decisions, such as modifying the budget, leaving the budget, or continuing to run the budget. The design of a budget system that has more value-added to the company is an important implication of this research.JEL Classification: M2, M40, M41DOI: https://doi.org/10.26905/jkdp.v24i3.4236